Bid’ah in Concept of Maslahah Mursalah and Istihsan According to Imam asy-Syathibi - Yahdi Dinul Haq; Hafizah Muchtia; Zia Alkausar Mukhlis (Institut Agama Islam Negeri Batusangkar, 2021)
The problem of fiqh that is always developing demands the realization of the argument that is the background of the legal basis for the act of fiqh. Istihsan and mashlahah mursalah are legal grounds accepted by the jurists, although there are some who reject their use. Asy-syathibi actually provides a unique interpretation by relating it to the term bid’ah which is the benchmark for the limits of the development of Islamic law so that it is always in accordance with the direction of the Shari'a.. The purpose of this paper is to explore the opinion of the Al-Imam asy-Syathibi regarding heresy as well as his opinion on the reasons some people base their bid’ah deeds with mashlahah mursalah and istihsan. So that the Al-Imam asy-Syathibi refused to use mashlahah mursalah and istihsan as the basis for heretical deeds.